Amelioration of polycystic ovarian morphology by Tokishakuyakusan in a PCOS rat model: association with bone morphogenetic protein 4 - Ueda, Mako; Osuka, Satoko; Yabuki, Atsushi; Miyake, Natsuki; Fujitsuka, Naoki; Nahata, Miwa; Tokita, Yohei; Ruan, Jiali; Bayasula,; Takeda, Takehiko; Seki, Tomomi; Sonehara, Reina; et al. (Frontiers in Endocrinology, 2026)
BackgroundPolycystic ovary syndrome (PCOS) is a common cause of irregular menstrual cycles and infertility. Current treatments primarily involve ovulation induction and sex steroid hormone therapy. Tokishakuyakusan (TSS) is a traditional Japanese medicine used for reproductive disorders. Bone morphogenetic protein 4 (BMP4), a regulator of follicular growth and steroidogenesis, may contribute to PCOS pathophysiology. This study aimed to investigate the effects of TSS on ovarian morphology, gene expression profiles, and steroidogenesis in a PCOS rat model.MethodsA Wistar rat model of PCOS was generated through prenatal dihydrotestosterone (DHT) exposure. Model rats were fed either a normal diet (DHT group) or a 3% TSS-supplemented diet (DHT+TSS group). Vehicle-treated control rats received a normal diet (vehicle group). Estrous cyclicity and ovarian histology were evaluated. Ovarian gene expression profiling and Western blot analyses were performed. Primary granulosa cells (GCs) isolated from healthy and model rats were treated with human follicle-stimulating hormone (FSH) and TSS to assess underlying mechanisms.ResultsPCOS-like phenotypes, including irregular estrous cycles and polycystic ovaries with atretic cyst-like follicles, were observed in the DHT group. Compared with the DHT group, the DHT+TSS group showed a reduced number of atretic cyst-like follicles and improved estrous cyclicity. Ovarian gene expression profiling revealed lower Bmp4 and inhibin-βa (Inhba) expression in the DHT+TSS group than in the DHT group. Consistent with these findings, BMP4 and inhibin βA protein levels were significantly decreased in the DHT+TSS group. In GCs from model rats, TSS treatment significantly reduced Bmp4 and Inhba expression and enhanced FSH-induced steroidogenic acute regulatory protein (Star) expression and progesterone production.ConclusionTSS ameliorated PCOS-like ovarian histopathology in prenatally DHT-treated rats and enhanced progesterone production by upregulating Star expression in GCs, accompanied by reduced BMP4 expression. These findings suggest that TSS may improve irregular estrous cycles and ovarian morphology in PCOS through the regulation of BMP4 signaling.